Quercetin alleviates rifampicin-induced hepatocyte injury by modulating the Hippo-YAP signaling pathway - Liu, Weiwei; Li, Hui; Lu, Weimin (Frontiers in Medicine, 2025)
ObjectiveTo investigate the protective effects of Quercetin, an antioxidant and anti-apoptotic flavonoid, against rifampicin (RFP)-induced hepatocyte injury via the Hippo-YAP signaling pathway.MethodsA rifampicin-induced hepatocyte injury model was established using HepaRG cells. HepaRG cells were divided into Control, RFP Model, Quercetin (15 μM), and Verteporfin (YAP inhibitor) groups. Cell viability was assessed by the CCK-8 assay, apoptosis by Annexin V/PI staining, and mitochondrial membrane potential (MMP) by TMRE staining. YAP localization was evaluated by immunofluorescence, and the expression of Hippo–YAP and apoptosis-related genes was analyzed by Western blot and qRT-PCR.ResultsQuercetin significantly improved cell viability, reduced apoptosis, and restored MMP in RFP-injured HepaRG cells. RFP activated the Hippo pathway by upregulating MST1 and LATS1, increasing YAP phosphorylation, and promoting apoptosis-related protein expression (Caspase-3, BAX), while downregulating anti-apoptotic BCL-2. Quercetin reversed these effects by inhibiting MST1/LATS1 activation, reducing YAP phosphorylation, and promoting its nuclear translocation. The protective effects were partially attenuated by Verteporfin, indicating Hippo–YAP pathway involvement.ConclusionQuercetin alleviates RFP-induced hepatocyte injury by suppressing Hippo pathway kinases MST1 and LATS1, reducing YAP phosphorylation, and enhancing YAP nuclear translocation, thereby improving MMP and inhibiting apoptosis.